(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The fundamental rights so in vogue after the redemocratization brought by the Federal Constitution of 1988 are drastically violated by the inertia of the powers and public authorities. There are numerous systematic unconstitutional omissions that seriously violate fundamental rights, generating in the State a vast structural failure that can not be restored by the constitutional remedies hitherto envisaged. The institute of the Unconstitutional State of Things, originated in Colombia and procedurally innovative, tries to overcome this failure, and because it is an activist deploy.